The Use of Vegetative Compatibility Tests for Identification of Biodiversity of Phytopathogenic Fungi - Krnjaja, Vesna S (Pesticides and Phytomedicine / Pesticidi i fitomedicina, 2013)
Visual assessment of phenotypes, performed when two strains of one fungal species are cultivated in a mixed culture on specific media, is known as vegetative or heterokaryotic compatibility or incompatibility test, which enables identification of fungal clones and their classification based on phylogenetic groups. Hyphae of strains that have identical alleles at all vic loci can anastomose into a form of a visible heterokaryon. Strains that divide compatible loci and can anastomose each other belong to a subpopulation termed the vegetative compatibility group (VCG), which is genetically distinguishable from other VCGs. Each VCG is specific regarding its host plant or related host groups and can, but does not have to be virulent on other hosts. Vegetative compatibility can be established in different ways, but complementary auxotrophic strains or strains formed by spontaneous mutation during nutrition, capable of forming a prototrophic heterokaryon are predominantly used. The nit mutants are considered excellent genetic markers for determination of vegetative compatibility and grouping of strains or clones of one fungus into the same or different VCGs. The ability only to determine whether strains are the same or not, but not the degree of their relatedness using VCG, is a limiting factor in analyses that could be performed. VCGs are the most efficient when they are employed to detect the presence of a specific strain in a population. This paper provides an overview of the importance of the phenomenon of vegetative compatibility. Vegetative compatibility is one of the most important genetic traits in ascomycetes by which one subpopulation can be identified as a distinct genetic group. Furthermore, the procedures for isolation, identification and determination of nit mutant phenotypes, and for identification of complementary strains and VCGs are described in detail.